Tratamento estético periodontal: revisão de literatura sobre alguns tipos de cirurgias - Dantas, Andrea Abi Rached [UNESP] (2012)
Currently, periodontal aesthetics has been prized for harmony of the smile. The clinical crown lengthening, gingival excess or altered passive eruption, is effectively corrected by periodontal surgery. The purpose of this paper is to show, through a literature review, some types of surgery on clinical crown lengthening and root coverage. Clinical crown lengthening is done to Change the size of the anterior teeth and to optimize the cosmetic result of treatment with new coronal restoration and other cosmetic dental care. In general, the treatment plan and the choice of operative technique begin with careful clinical examination. Recessions tissue can be defined as a displacement of the gingival margin toward the junction mucogingival exposing the root surface. These, when present, impacting on patient comfort by providing the occurrence of cervical dentin hypersensitivity, and the esthetic, the amendment of the gum line. Successful treatment of recessions is based on knowledge of its etiology and assessment of predictability of surgical techniques that aim to root coverage. Through literature review, we can conclude that the types of surgery most often used are: 1) to increase the clinical crown, gingivectomy, flap surgery and gingivoplasty osteotomy, and 2) for root coverage, the use will depend on the amount of gum keratinized and especially the classification of Miller.